Semi-Automated Correction Tools for Mathematics-Based Exercises in MOOC Environments - Corbi, Alberto; Burgos, Daniel (International Journal of Interactive Multimedia and Artificial Intelligence, 2017)
Massive Open Online Courses (MOOCs) allow the participation of hundreds of students who are interested in a wide range of areas. Given the huge attainable enrollment rate, it is almost impossible to suggest complex homework to students and have it carefully corrected and reviewed by a tutor or assistant professor. In this paper, we present a software framework that aims at assisting teachers in MOOCs during correction tasks related to exercises in mathematics and topics with some degree of mathematical content. In this spirit, our proposal might suit not only maths, but also physics and technical subjects. As a test experience, we apply it to 300+ physics homework bulletins from 80+ students. Results show our solution can prove very useful in guiding assistant teachers during correction shifts and is able to mitigate the time devoted to this type of activities.
Keywords: assignments; semiautomated correction; maths; physics; framework; Emerging; IJIMAI